2017
DOI: 10.1073/pnas.1704962114
|View full text |Cite|
|
Sign up to set email alerts
|

IgH isotype-specific B cell receptor expression influences B cell fate

Abstract: Ig heavy chain (IgH) isotypes (e.g., IgM, IgG, and IgE) are generated as secreted/soluble antibodies (sIg) or as membrane-bound (mIg) B cell receptors (BCRs) through alternative RNA splicing. IgH isotype dictates soluble antibody function, but how mIg isotype influences B cell behavior is not well defined. We examined IgH isotype-specific BCR function by analyzing naturally switched B cells from wild-type mice, as well as by engineering polyclonal γ1/γ1 andε/ε mice, which initially produce IgG1 or IgE from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…A new mouse model has been generated to force membrane IgE expression from early B cell development ( 105 ), similarly to εKI mice (Figure 2 ), but using a different strategy and a mouse Cε gene. These animals have also a strong blockade at the pro-B cell stage, again showing that Cε gene cannot support B cell development.…”
Section: Discussionmentioning
confidence: 99%
“…A new mouse model has been generated to force membrane IgE expression from early B cell development ( 105 ), similarly to εKI mice (Figure 2 ), but using a different strategy and a mouse Cε gene. These animals have also a strong blockade at the pro-B cell stage, again showing that Cε gene cannot support B cell development.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when interpreting the data regarding the antigen‐independent function of murine mIgE‐BCRs, one has to consider that all in vitro experiments in these studies were done with exogenously expressed mIgE and hence the amounts of cell surface mIgE that were achieved in these experiments did not necessarily match those observed in native cells. This fact may be important, since a recent study, which compared the tonic (ie, antigen‐independent) signaling capacities of different mIg isotypes in mouse model systems, reported that the expression of mIgE from the endogenous Ig ε heavy chain locus with all its regulatory genetic elements leads to a very low expression of mIgE‐BCRs on the cell surface, much lower than that of mIgM‐ and mIgG‐containing BCRs . This low abundance of cell surface‐expressed mIgE‐BCRs was associated with poor survival of the cells, which most likely was caused by an insufficient tonic mIgE‐BCR maintenance signal.…”
Section: Unique Features Of the Mige‐bcr Control The Biology Of Ige‐smentioning
confidence: 99%
“…The majority of IgE + B cells were found to differentiate into PCs that were primarily short-lived ( Yang et al, 2014 ). The various distinct features of IgE responses have been attributed to unique properties of the IgE B cell receptor (BCR; Achatz-Straussberger et al, 2008 ; Haniuda et al, 2016 ; Laffleur et al, 2015 ; Tong et al, 2017 ; Vanshylla et al, 2018 ; Yang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%